Factors that influence saving habits among Gen Y: Case study on students of Politeknik Sultan Azlan Shah - Hasni, Hashim (2014)
The purpose of this study is investigating the significant relationship between factors that influence saving habits among Gen Y (students of the Politeknik Sultan Azlan Shah). This study was performed on four (4) different department in Politeknik Sultan Azlan Shah which are Commerce Department, Mechanical Engineering Department, Electrical Engineering Department and Civil Depart Department. The objective of this study is to investigate the saving habits of Gen Y (students at Politeknik Sultan Azlan Shah) and to identify which factors will be the most influential among financial literacy, parental socialization, peer influence and self control. The study used saving habits as a dependent variable and the independent variables used are financial literacy (fl), parental socialization (ps), peer influence (pi) and self control (sc). Person Correlation Coefficient analysis has been applied to examine the significant relationship between independent variables with dependent variables. The results show that Parental Socialization played the most important roles in influence saving habits among Gen Y, and the weakest is self control.